Flexible Sector Detector-based Mismatch Supply Voltage In Direct Torque Control Doubly Fed Induction Machine: An Experimental Validation - Muhammad Zaid Aihsan; Auzani Jidin; Muhammad Mokhzaini Azizan; Muhammad Izuan Fahmi; Khairunnisa Hasikin (Elsevier, 2024)
Volume 74, Pages 689 - 704